Mutu Organoleptik Mie Kering Yang Diproduksi Dari Tepung Tulang Ikan Dan Tepung Wortel Sebagai Pensubtitusi Tepung Terigu - Safrianto S Maruka; Gatot Siswohutomo; Rostiati Dg Rahmatu (Mitra Sains, 2016)
The utilization of fish bone waste so far is processed as mixture of fodder and some into flour. It is less used for humans needs. The processed products food to be substituted of flour a bone of fish products are noodles. This research aims to determine the substitution level on fish bone flour and carrot flour that producing good quality in noodles and find out consumer acceptance toward the addition of fish bone flour and carrot flour have been substituted. The research was designed by employing complete random design with factorial pattern. The parameter of organoleptic quality test was on color, scent, taste, texture and fondness as a whole. The research result reveals that the addition of fish bone flour and carrot flour in treatment A1B2 provides quality value on color, scent and texture that can be accepted by panel.